MORALITY BEYOND CONTRACTUALISM - Brito, Adriano Naves de (Princípios: Revista de Filosofia (UFRN), 2015)
In this paper, I intend to outline a moral concept which could be the bases for an immanent theory of values which is sustained by the economy of feelings involved in the moral confrontation characteristic of the social life of animals possessing a complex nervous system, as is particularly the case with certain species of mammals, including homo sapiens. What gives a moral dimension to these feelings is the way in which they interfere with and determine the mutual behaviour of individuals within a group, and it is through this process that values are devised, sustained and transmitted. The route I will take is as follows: I will begin by discussing the problem of normativity, on the basis of an updating of the naturalist fallacy by way of the genetic fallacy, and from the point of view of a theory of value. This means that I will not approach the issue directly via the problem of duty, but by showing that it is connected to, and better understood within, a perspective of value. The choice in a moral theory of the measure of what is good in it has fundamental implications for the concept of duty, which is at the heart of of any discussion concerning normativity. This connection shall be clarified. I will then dispute the thesis that the individual (in the civil and legal sense attributed to the term by the Enlightenment) is an adequate starting-point for practical philosophy, and criticise the limits which tradition has placed on what can be considered moral whilst, by the same token, criticising classical contractualist concepts of morality which has been the bases for the majority of moral approaches in contemporary philosophy including for naturalistic ones.